Tropical cloud-radiative changes contribute to robust climate change-induced jet exit strengthening over Europe during boreal winter - Nicole Albern (Institute of Meteorology and Climate Research—Department Troposphere Research, Karlsruhe Institute of Technology); Aiko Voigt (Department of Meteorology and Geophysics, Faculty of Earth Sciences, Geography and Astronomy, University of Vienna); Joaquim G Pinto (Institute of Meteorology and Climate Research—Department Troposphere Research, Karlsruhe Institute of Technology) (Environmental Research Letters, 2021)
The abstract is available here: https://uscholar.univie.ac.at/o:1604028 The abstract is available here: https://uscholar.univie.ac.at/o:1604028